Benchmarking postoperative outcomes after open liver surgery for cirrhotic patients with hepatocellular carcinoma in a national cohort. Issue 8 (August 2022) - Famularo, Simone; Russolillo, Nadia; Donadon, Matteo; Cipriani, Federica; Ardito, Francesco; Perri, Pasquale; Giani, Alessandro; De Stefano, Francesca; Lai, Quirino; Molfino, Sarah; Zanello, Matteo; Iaria, Maurizio; et al.
Abstract: Background: Benchmark analysis for open liver surgery for cirrhotic patients with hepatocellular carcinoma (HCC) is still undefined. Methods: Patients were identified from the Italian national registry HE.RC.O.LE.S. The Achievable Benchmark of Care (ABC) method was employed to identify the benchmarks. The outcomes assessed were the rate of complications, major comorbidities, post-operative ascites (POA), post-hepatectomy liver failure (PHLF), 90-day mortality. Benchmarking was stratified for surgical complexity (CP1, CP2 and CP3). Results: A total of 978 of 2698 patients fulfilled the inclusion criteria. 431 (44.1%) patients were treated with CP1 procedures, 239 (24.4%) with CP2 and 308 (31.5%) with CP3 procedures. Patients submitted to CP1 had a worse underlying liver function, while the tumor burden was more severe in CP3 cases. The ABC for complications (13.1%, 19.2% and 28.1% for CP1, CP2 and CP3 respectively), major complications (7.6%, 11.1%, 12.5%) and 90-day mortality (0%, 3.3%, 3.6%) increased with the surgical difficulty, but not POA (4.4%, 3.3% and 2.6% respectively) and PHLF (0% for all groups). Conclusion: We propose benchmarks for open liver resections in HCC cirrhotic patients, stratified for surgical complexity. The difference between the benchmark values and the results obtained during everyday practice reflects the room for potential growth, with the aim to encourage constant improvement among liver surgeons.